Fundamentals of molecular spectroscopy - Colin N Banwell; Mccash Elaine M (New Delhi Affiliated East-West Press Private Limited, 2024)
Fundamentals of Molecular Spectroscopy, 6th Edition by C.N. Banwell and E.M. McCash provides a clear and comprehensive introduction to the principles and applications of molecular spectroscopy. This edition emphasizes theoretical foundations while offering practical examples and problems to aid student understanding. Covering rotational, vibrational, electronic, and Raman spectroscopy, the book is ideal for undergraduate and postgraduate courses in chemistry and physics. With updated content reflecting modern developments, it remains a trusted resource for learning spectral techniques. The lucid explanations make complex concepts accessible even to first-time learners.
Keywords: Analytical Chemistry